Investigating alveolar myofibroblasts and alveolar myofibroblast-like cells during lung development and regeneration - Khadim, Ali; Justus Liebig University Giessen (My University, 2025)
This study uncovers the pivotal role of alveolar myofibroblasts (AMFs) in lung development, homeostasis, and regeneration. Using genetic lineage tracing, scRNA-seq, and 3D-histology, we demonstrate that AMFs not only orchestrate alveolar formation during early development but also persist into adulthood as a latent hedgehog-responsive population. Upon injury—whether pneumonectomy, cigarette smoke, or influenza A virus-induced ARDS—these cells re-engage developmental programs to drive alveolar regeneration. However, their prolonged activation under pathological conditions may shift them toward fibrotic remodeling. Positioned at a crossroads between repair and disease, AMFs emerge as key players in lung biology and compelling targets for regenerative interventions.
Keywords: alveolar regeneration; mesenchymal niche cells; single-cell transcriptomics; fate mapping; influenza virus; alveolar myofibroblasts; ddc:610; ddc:570